2022
DOI: 10.2196/36056
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Unmet Needs of Individuals With Mental Disorders: Scoping Review on Peer-to-Peer Web-Based Interactions

Abstract: Background An increasing number of online support groups are providing advice and information on topics related to mental health. Objective This study aimed to investigate the needs that internet users meet through peer-to-peer interactions. Methods A search of 4 databases was performed until August 15, 2022. Qualitative or mixed methods (ie, qualitative and quantitative) studies investigating interactions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 160 publications
0
4
0
Order By: Relevance
“…Qualitative content analysis was used to understand experiences presented in the posts, while quantitative analysis was used to provide numerical descriptions of the data and explore relationships between needs and trends. We coded the interactions between forum users that revealed their needs related to hospitalization in psychiatric units using a codebook developed in our previous study [ 66 ]. Coding quality was ensured by training all the coders.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative content analysis was used to understand experiences presented in the posts, while quantitative analysis was used to provide numerical descriptions of the data and explore relationships between needs and trends. We coded the interactions between forum users that revealed their needs related to hospitalization in psychiatric units using a codebook developed in our previous study [ 66 ]. Coding quality was ensured by training all the coders.…”
Section: Methodsmentioning
confidence: 99%
“…Moderators often only receive basic training from the organisation for whom they volunteer and are not bound to engage in any form of clinical supervision. Evidence has suggested that unmoderated communities may experience negative effects such as distortion of information and negative social interactions (Kraut and Resnick, 2012;Young, 2013;Storman et al, 2022). Previous research has suggested that OMHC users perceive the OMHC to give them a sense of community, allowing them to communicate with like-minded individuals (Rathbone et al, 2020).…”
Section: Moderatorsmentioning
confidence: 99%
“…Previous reviews have identified and described mental health forum user experiences. For example, it is clear that online forum-based interventions for mental health are feasible and viewed as acceptable by most users and meet some users' needs for informational and social support [23][24][25]. However, there have been recent calls for mechanistic research to better understand the processes that underpin the effects of online forums to inform innovations in forum design and implementation [26].…”
Section: Objectivesmentioning
confidence: 99%
“…Our decision to search from 2019 onward was informed by a recent comprehensive review of digital health interventions that identified both a shift in the online context of health service delivery as a result of the COVID-19 pandemic and a notable increase in relevant literature in the same year [29]. It is also likely that pre-2019 articles are captured in related systematic reviews [23,24]. The scope of this synthesis was also informed by engagement with a public and patient involvement group comprising forum staff and users.…”
Section: Stage 1: Define the Scope Of The Synthesismentioning
confidence: 99%